Variation in Antarctic Petrel Foraging Ecology: Not All Individuals Specialize on Krill - Descamps, S.; Harris, S. M.; Fluhr, J.; Bustamante, P.; Cherel, Y.; Trevail, A. M.; Brault-Favrou, M.; Patrick, S. C. (Frontiers in Marine Science, 2022)
Individual heterogeneity in foraging behaviour determines how individuals and populations respond to changes in the availability and distribution of resources. Antarctic krill Euphausia superba is a pivotal species in Southern Ocean food webs and an important target for Southern Ocean fisheries. Changes in its abundance could dramatically impact marine predators, with effects depending on the extent to which all individuals rely on krill as prey. The Antarctic petrel Thalassoica antarctica is a high latitude seabird thought to be dependent on krill in part of its breeding range. Here, by combining fine-scale GPS tracking of petrel foraging trips with diet data, we examined the level and consistency of inter-individual variation in foraging strategies in breeding Antarctic petrels in Dronning Maud Land, Antarctica, and assessed whether all individuals share a similar reliance on Antarctic krill. We found that Antarctic petrels showed high levels of repeatability in their diet and foraging movements at sea, indicating consistent individual differences in foraging strategies. During consecutive foraging trips, petrels tend to make trips of similar lengths and durations to reach similar terminal locations and to feed on similar prey. These individual differences in diet were spatially structured, with individuals travelling towards the west consuming a more fish-based diet. These different foraging tactics did not appear to be associated with different costs and/or benefits as adult body mass, chick survival and chick growth were unrelated to birds’ foraging movements and diet. Our results show that, even if a large part of the population may be dependent on krill, some individuals specialize on fish. Such inter-individual variation in foraging suggests that this population could be more resilient to changes in the marine environment, such as a decline in krill abundance or a shift in krill distributions.